Internationalisation of education in the age of global pandemic: Challenges and prospects - Tirivangasi, Happy Mathew; Nyahunda, Louis; Mabila, Thembinkosi (Technium Social Sciences Journal, 2021)
The outbreak of corona virus has created all sorts of ramifications for higher education in South Africa and the world at large. In this case not only the faculty of humanities was affected but all the faculties were affected as the disease has made the plight of students to be a serious concern. Students the world over have been left in a sticky situation amid the corona virus outbreak as government policies and social distancing measures lead to campuses closing. This has resulted in both local and international students leaving for their home. The situation remains uncertain on how the government is going to treat the migrant students and staff who come from all over the world. This chapter highlights some of the challenges that comes with internationalisation of education like varying cultures, xenophobia, untrained teaching staff; students’ assessment and compatibility with Online Distance Learning (ODL). These are challenges which are going to be faced with different universities in South Africa and across the globe. Hence, we advocate for different universities to take pandemic pedagogy as an opportunity to offer and adjust their programmes to online teaching. In this chapter we advance the adoption of ADDIE model as an instrument to use in designing effective online curriculum. These are a snippet view of how institutions can overcome the lockdown and carter as well for their international students in the days of uncertainty regarding mobility in the future. However, with good strategies stated above the future of education is certain. The pandemic is both a curse and an opportunity for universities to adjust to ODL and enhance their preparedness.